2013
DOI: 10.1007/s10495-013-0927-2
|View full text |Cite
|
Sign up to set email alerts
|

Targeting elongation factor-2 kinase (eEF-2K) induces apoptosis in human pancreatic cancer cells

Abstract: Pancreatic cancer (PaCa) is one of the most aggressive, apoptosis-resistant and currently incurable cancers with a poor survival rate. Eukaryotic elongation factor-2 kinase (eEF-2K) is an atypical kinase, whose role in PaCa survival is not yet known. Here, we show that eEF-2K is overexpressed in PaCa cells and its down-regulation induces apoptotic cell death. Rottlerin (ROT), a polyphenolic compound initially identified as a PKC-δ inhibitor, induces apoptosis and autophagy in a variety of cancer cells includin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
59
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 80 publications
(62 citation statements)
references
References 51 publications
2
59
0
1
Order By: Relevance
“…Plated cells were transfected with double-stranded siRNA targeting the mRNA of the serotonergic receptors (5-HT-1) subtype –B or –D (Sigma-Aldrich, St. Louis, MO), or transfected with control (non-silencing) siRNA; (5′-AAUUCUCCGAACGUGUCACGU-3′) [34], [35] (Sigma-Aldrich, St. Louis, MO). siRNA targeting tissue transglutaminase (TG2) (Qiagen, Valencia, CA) were also employed [35]. Cells were transfected with either siRNA, at a final concentration of 25–50 nM for 72 h, using HiPerFect Transfection Reagent (Qiagen, Valencia, CA) according to the manufacturer's protocol.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Plated cells were transfected with double-stranded siRNA targeting the mRNA of the serotonergic receptors (5-HT-1) subtype –B or –D (Sigma-Aldrich, St. Louis, MO), or transfected with control (non-silencing) siRNA; (5′-AAUUCUCCGAACGUGUCACGU-3′) [34], [35] (Sigma-Aldrich, St. Louis, MO). siRNA targeting tissue transglutaminase (TG2) (Qiagen, Valencia, CA) were also employed [35]. Cells were transfected with either siRNA, at a final concentration of 25–50 nM for 72 h, using HiPerFect Transfection Reagent (Qiagen, Valencia, CA) according to the manufacturer's protocol.…”
Section: Methodsmentioning
confidence: 99%
“…pyrophosphate, 1 mM Na 3 VO 4 and 10% glycerol, containing proteinase and phosphatase inhibitors (Roche Applied Science, Indianapolis)] were added to each well. The cell lysates were collected, and RPPA was processed as described before [35].…”
Section: Methodsmentioning
confidence: 99%
“…Recently, emerging evidence has revealed that eukaryotic elongation factor 2 kinase (eEF2K) is a potential molecular driver in several cancers, including pancreatic, brain and breast cancer [1116]. eEF2K is the only calcium/calmodulin activated member of the α-kinase family and is considered an atypical kinase since its catalytic domain is not structurally similar to those of conventional protein kinases [17, 18].…”
Section: Introductionmentioning
confidence: 99%
“…eEF2K promotes cell survival in conditions of nutrient deprivation, hypoxia and metabolic stress by regulating the rate of translation [24]. Recently, eEF2K was shown to promote cell proliferation, cell migration, invasion, epithelial-mesenchymal transition (EMT) and TNBC tumorigenesis and progression through modulating the cell cycle (G1/S transition) by regulating cyclin D1, c-myc, PI3K/Akt, Src/Fak and insulin-like growth factor receptor (IGFR) signaling [11, 13, 14, 16]. Therapeutic targeting of eEF2K triggers apoptosis and suppresses TNBC tumor growth, in addition to and increased doxorubicin and paclitaxel efficacy [16].…”
Section: Introductionmentioning
confidence: 99%
“…siRNAs have been used with breast cancer therapeutics to specifically target C-X-C chemokine receptor 4 [61,62], elongation factor 2 kinase [63], Aurora kinase A [64], beta 3 integrin [65], B-cell chronic lymphocytic leukemia (CLL)/lymphoma 11A gene [66], HER2 [67], tumor p53 gene [68], adenosine triphosphate-binding cassette E1 and eukaryotic release factor 3 [69].…”
Section: Sirnasmentioning
confidence: 99%